Influence of oceanic small-scale variability associated with the Gulf Stream on air-sea interactions and impact on North Atlantic atmospheric variability - Piazza, Marie (HAL CCSD, 2015)
This thesis aims at analyzing the influence of small-scale spatial variability of the sea surface temperature (SST) over an oceanic front on the climate variability at mid-latitudes. We focus on the effect of the Gulf Stream SST front on the marine atmospheric boundary layer and the free troposphere, and on the large-scale atmospheric variability over the Euro-North Atlantic basin. We follow an approach based on numerical experiments with a high resolution (approximately 50 km at mid-latitudes) global atmospheric model, first forced with daily observed SST then coupled with a dynamical oceanic model. The first part of this thesis deal with the effects of small-scale oceanic forcing on the atmosphere locally and on the large-scale variability over the North Atlantic, at seasonal to inter-annual timescales. Two ensembles (with 4 members) of forced simulations are performed, the first one with global SST at high resolution (0.25°) and the other one with smoothed SST at 4° in the Gulf Stream region, in order to filter the small-scale spatial variability on the frontal area. Locally, the model captures the response of the SST small-scale forcing on the small-scale spatial variability of wind-speed at surface during winter, but with an underestimation of about 1/3 compared to the observations. The evaluation of the model compared to reanalysis shows that the large-scale spatial variability (jet stream, weather regimes) is well reproduce at mid-latitudes over North Atlantic and Europe. Comparison between the two experiments shows that the influence of small-scale spatial variations of the SST in the Gulf Stream region deeply affect the atmospheric column and reach the free troposphere (wind convergence at surface due to pressure adjustment in the boundary layer, turbulent heat fluxes at surface increase due to boundary layer destabilization, convective precipitations increase on the southern (warmer) part of the front and decrease on the northern (cooler) part). Locally, extra-tropical storms show an increase of the ...